1H‐MRS measured ectopic fat in liver and muscle is associated with the metabolic syndrome in Danish girls but not in boys with overweight and obesity. (14th September 2016) - Nissen, A.; Fonvig, C. E.; Chabanova, E.; Bøjsøe, C.; Trier, C.; Pedersen, O.; Hansen, T.; Thomsen, H. S.; Holm, J. ‐C.
Summary: Background: The metabolic syndrome (MetS) is a complication to overweight and obesity, which can be observed already in childhood. Ectopic lipid accumulation in muscle and liver has been shown to associate with the development of insulin resistance and dyslipidemia. Thus, the interaction between MetS and ectopic fat may offer clinical relevance. Objectives: To investigate the prevalence of MetS, or components hereof, and ectopic fat accumulation in liver and skeletal muscle tissue in children, as well as interactions between these. Methods: Two‐hundred‐and‐sixteen children and adolescents (95 boys) with overweight/obesity were investigated, as well as 47 controls (22 boys) with normal weight. The assessments included anthropometry, fasting blood biochemistry and blood pressure measurements. Liver and muscle lipid contents were assessed by proton magnetic resonance spectroscopy. Results: We observed an odds ratio in girls with overweight/obesity of 12.2 (95% confidence interval: [3.8; 49.0]) for exhibiting MetS when hepatic steatosis was present, whereas no association was observed in boys with overweight/obesity (odds ratio 0.7 [0.2; 2.7]). The odds ratio of exhibiting MetS in the presence of muscular steatosis was 3.5 [1.4; 9.5] in girls with overweight/obesity and 1.0 [0.2; 5.6] in boys with overweight/obesity. Similar results were seen for girls with overweight/obesity exhibiting concurrent hepatic and muscular steatoses. Conclusion: Hepatic and muscular steatoses were associated with MetS among girls, but not among boys with overweight/obesity.